2013
DOI: 10.1093/bioinformatics/btt374
|View full text |Cite
|
Sign up to set email alerts
|

A new framework for computational protein design through cost function network optimization

Abstract: The combined pipeline used to generate energetic models (based on a patched version of the open source solver Osprey 2.0), the conversion to CFN models (based on Perl scripts) and CFN solving (based on the open source solver toulbar2) are all available at http://genoweb.toulouse.inra.fr/~tschiex/CPD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 48 publications
0
85
0
1
Order By: Relevance
“…For example, in a recent study [53••], Simoncini et al compared their provable optimization algorithm implemented in the Toulbar2 program [54, 55] vs. the heuristic simulated annealing (SA) algorithm implemented in the Rosetta program using a GMEC-model. They found that, in a set of 100 test protein designs, SA often fails to compute the optimal answer even after running hundreds of times.…”
Section: Provable Vs Heuristic Algorithmsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in a recent study [53••], Simoncini et al compared their provable optimization algorithm implemented in the Toulbar2 program [54, 55] vs. the heuristic simulated annealing (SA) algorithm implemented in the Rosetta program using a GMEC-model. They found that, in a set of 100 test protein designs, SA often fails to compute the optimal answer even after running hundreds of times.…”
Section: Provable Vs Heuristic Algorithmsmentioning
confidence: 99%
“…Promising improvements in the performance of protein design optimization algorithms for the GMEC-model were recently reported by Thomas Schiex and co-workers [53••–55, 68]. Their protein design optimization algorithm exploits weighted constraint satisfaction (WCSP) techniques, including fast soft local consistencies for bounding, an advanced branch and bound implementation, and sophisticated ordering techniques, to compute the GMEC significantly faster than competing approaches [54].…”
Section: Progress In Optimization Algorithms For the Gmec-modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, these heuristic methods can be trapped into local minima and may lead to poor quality of the final solution. On the other hand, several exact and provable search algorithms which guarantee to find the GMEC solution have been proposed, such as Dead-End Elimination (DEE) [6], A* search [21,22,7,35], tree decomposition [32], branch-and-bound (BnB) search [14,31,3], and BnB-based linear integer programming [1,18].…”
Section: Introductionmentioning
confidence: 99%